An investigation into the effectiveness of corporate sustainability programmes and initiatives in the agricultural sector : the case of British American Tobacco Zimbabwe - Nyanyirai, Stanley (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.